A Network Investigation on Idiopathic Hypogonadotropic Hypogonadism in China - Weiwei Zhao; Hongying Ye; Xiaolong Zhao; Zhaoyun Zhang; Shouyue Sun; Yiran Jiang; Min He; Cheng Xu; Renming Hu; Yiming Li (International Journal of Endocrinology)
Idiopathic hypogonadotropic hypogonadism (IHH) is a rare condition in which puberty does not take place naturally. We aimed to develop and follow an internet-based cohort and to improve our understanding of the disease. We established an internet-based questionnaire survey. A total of 74 male IHH patients were recruited from the Chinese largest IHH network social group. The clinical symptoms before treatment mainly included small testis, underdeveloped secondary sexual characteristics, and sexual dysfunction. After treatment, the penis length, testicular volume, external genital organ development, pubic hair, beard, laryngeal prominence, erection, and spermatorrhea were improved significantly (P<0.001). 18.9% of the patients completed fertility; however, more than half of the patients still complained of poor happiness and low physical strength. In addition, improvements in penis and pubic hair development, testosterone normalization and the physical strength in IHH patients who received gonadotropin and androgen replacement therapy were better than in those who received single gonadotropin therapy (P<0.05 for all). In conclusion, disease-specific network investigation can be used as an alternative method of medical research for rare diseases. The results of our cross-sectional study showed the effectiveness of hormone replacement therapy for IHH and implied that gonadotropin and androgen replacement therapy may be superior to gonadotropin treatment alone.